Drug-Related Problems Detected in Australian Community Pharmacies: The PROMISe Trial - Williams, M.; Peterson, G.; Tenni, P.; Bindoff, I.; Curtain, C.; Hughes, J.; Bereznicki, L.; Jackson, S.; Kong, D.; Hughes, Jeffery (Harvey Whitney Book Company, 2011)
BACKGROUND: Drug-related problems (DRPs) are a major burden on health care systems. Community pharmacists are ideally placed to detect, prevent, and resolve these DRPs. OBJECTIVE: To determine the number and nature of DRPs detected and clinical interventions performed by Australian community pharmacists, using an electronic system. METHODS: An electronic documentation system was designed and integrated into the existing dispensing software of 186 pharmacies to allow pharmacists to record details about the clinical interventions they performed to prevent or resolve DRPs. Participating pharmacies were randomly allocated to 3 groups: group 1 had documentation software, group 2 had documentation software plus a timed reminder to document interventions, and group 3 had documentation software, a timed reminder, and an electronic decision support prompt. Pharmacists classified DRPs, entered recommendations they made, and estimated the clinical significance of the intervention. An observational substudy that included pharmacies without any documentation software was completed to verify intervention rates.RESULTS: Over 12 weeks, 531 participating pharmacists recorded 6230 clinical interventions from 2,013,923 prescriptions, with a median intervention rate of 0.23% of prescriptions. No significant differences were seen between the 3 groups that used documentation software; as expected, however, the pharmacies that used this software had a significantly higher documentation rate compared to the pharmacies without documentation software. The most common interventions were related to drug selection problems (30.8%) and educational issues (24.4%). Recommendations were often related to a change in therapy (40.0%), and 41.6% of interventions were self-rated as highly significant. Drug groups most commonly subject to an intervention included antibiotics, glucocorticoids, nonsteroidal antiinflammatory drugs, and opioids. CONCLUSIONS: The documentation system allowed for the determination of the frequency and types of DRPs, as well as the recommendations made to resolve them in community pharmacy practice. Use of the software, including its electronic prompts, significantly increased the documentation of interventions by pharmacists.